2015
DOI: 10.1155/2015/295706
|View full text |Cite
|
Sign up to set email alerts
|

Keishibukuryogan, a Traditional Japanese Medicine, Inhibits Platelet Aggregation in Guinea Pig Whole Blood

Abstract: Effects of keishibukuryogan (KBG) on platelet aggregation were investigated. To ensure the specificity of KBG, tokishakuyakusan (TSS) and kamisyoyosan (KSS), which are known to have platelet aggregation-inhibiting effects, and rikkunshito (RKT) and shakuyakukanzoto (SKT), which are considered to be devoid of such effects, were used for comparison. The platelet aggregation of each test drug was measured by the screen filtration pressure method using whole blood of guinea pigs and expressed as a collagen-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In the present study, we observed that GBH treatment significantly increased plasma serotonin levels while significantly decreasing corticosterone levels in reserpine-treated mice, relative to levels observed in control mice. Although plasma serotonin levels may represent release from both the central nervous system and platelets, GBH is known to suppress blood aggregation—a process that activates serotonin release [ 39 , 40 ]. Thus, it is unlikely that platelets represented the major source of serotonin release in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that GBH treatment significantly increased plasma serotonin levels while significantly decreasing corticosterone levels in reserpine-treated mice, relative to levels observed in control mice. Although plasma serotonin levels may represent release from both the central nervous system and platelets, GBH is known to suppress blood aggregation—a process that activates serotonin release [ 39 , 40 ]. Thus, it is unlikely that platelets represented the major source of serotonin release in our study.…”
Section: Discussionmentioning
confidence: 99%
“…19 The clinical usage of TSS is empirical, and the molecular mechanisms underlying the purported efficacy of TSS are limited. Regarding biological effects of TSS, vascular smooth muscle relaxation, 20 inhibition of platelet aggregation 21 and anti-inflammatory effect including induction of regulatory T cell 22,23 have been reported previously. This study is the first to report a potential mechanism to explain a documented improvement in pregnancy maintenance in mice upon dietary exposure to TSS.…”
Section: Discussionmentioning
confidence: 73%
“…GZFLW, as a traditional Chinese medicine, owns many years of history for the treatment of endometriosis and has also been used for other diseases in animal models, such as dietary obesity in rats [23], improvement of microcirculation in mice [24], and inhibition of platelet aggregation in Guinea Pig [25]. However, due to the complexity of traditional Chinese medicine ingredients, its molecular biology mechanism is not yet clear.…”
Section: Discussionmentioning
confidence: 99%